NILAI TAMBAH RANTAI PASOK KOPI PADA KOPERASI PRODUSEN KOPI MARGAMULYA DI KECAMATAN PENGALENGAN KABUPATEN BANDUNG: KOMPARASI ANTARA PETANI DAN PENGOLAH KOPI - Kirana, Sesilia; Karyani, Tuti (Jurnal AGRISEP, 2017)
TThe value added is the value of a product that occurs due to different stages of activity conducted on the product. Cooperative Of Coffee Producers Margamulya (CCPM) is one of the producers of java preanger arabica coffee which performs the stages of activity causing transformation of product form, start from cherry to green bean with PT Taman Delta Indonesia as marketing channel. Therefore interesting to be studied a) coffee supply chain of PKPM; and b) The difference of value added that occurs between the farmers who do and do not do the processing of horn skin. The method used in this research was qualitative method by using value added analysis. The result show that in KPKM’s supply chain, with PT Taman Delta Indonesia as marketing channel, KPKM’s source of raw material are members that supply cherry and processer members that supply horn skin. The value added that obtained by members that sell cherry to KPKM’s are Rp4.558,00. The value added that obtained by processer members that sell horn skin to KPKM’s are Rp5.036,74. Members who do the processing of horn skin before selling to KPKM get higher profits because in addition to profit that gained from selling cherry, processer members get value added due to product transformation